PUSAT INDUSTRI FASHION BATIK DAN SASIRANGAN KHAS TABALONG - Puteri, Elyda Zaiyantina; Nurfansyah, Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
The design of the Fashion Industry Batik and Sasirangan Tabalong Center was motivated by the government's desire to introduce more typical fabrics from Tabalong Regency. This desire makes the potential to develop a Fashion Industry Center that focuses on batik makers and visitors. The purpose of this design is to get a design that makes batik can increase creativity and innovation in making Batik and Sasirangan fabric motifs and fashion products and visitors can experience. By applying the Cultural to Creativity concept combined with 4P creativity concepts and using Architectural Programming methods. The application of cultural concepts is in the shape and exterior finishing of buildings, the application of the concept of creativity is applied to circulation, mass management, and interior.